Нові місцезнаходження Pisolithus arrhizus (Scop.) Rauschert (Sclerodermataceae) в Україні - ГЕЛЮТА, ВАСИЛЬ ПЕТРОВИЧ; ДЖАГАН, ВЕРОНІКА ВОЛОДИМИРІВНА; ХОДОСОВЦЕВ, ОЛЕКСАНДР ЄВГЕНОВИЧ; КОСТІКОВ, ІГОР ЮРІЙОВИЧ; ВОЛГІН, СЕРГІЙ ОЛЕКСАНДРОВИЧ; БОЙКО, МИХАЙЛО ФЕДОСІЙОВИЧ; ТИХОНЕНКО, ЮРІЙ ЯКОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Нові місцезнаходження Pisolithus arrhizus (Scop.) Rauschert (Sclerodermataceae) в Україні